2017
DOI: 10.4103/ijciis.ijciis_100_16
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptic malignant syndrome in the trauma intensive care unit: Diagnosis and management of a rare disease in a challenging population

Abstract: Neuroleptic malignant syndrome (NMS) is a life-threatening neurological disorder associated with the use of antipsychotic medications. Many of its classic signs, such as fever and altered mental status, are nonspecific in trauma intensive care unit (ICU) patients, and its rarity makes it a difficult diagnosis in this population. However, delays in treatment can be costly both in terms of hospital resources and patient outcomes. We herein report a case of a 54-year-old trauma patient with NMS precipitated by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 9 publications
(18 reference statements)
1
11
0
Order By: Relevance
“…Whereas dantrolene is commonly used for spasticity and malignant hyperthermia by ED providers, neurologists and intensivists favor bromocriptine as the medical therapy for management of NMS. This change in medical therapies used for NMS management during a hospital course has been reported previously 1,11…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Whereas dantrolene is commonly used for spasticity and malignant hyperthermia by ED providers, neurologists and intensivists favor bromocriptine as the medical therapy for management of NMS. This change in medical therapies used for NMS management during a hospital course has been reported previously 1,11…”
Section: Discussionsupporting
confidence: 65%
“…Recent literature suggests that both diagnosis and treatment of NMS remain challenging 11,18. While NMS is primarily recognized by hyperthermia and peripheral muscle rigidity, presentation can often vary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative study of 166 psychiatric patients with and without substance use history treated with antipsychotics revealed that four or 5.1% of cocaine users developed NMS compared to none of the non-cocaine users [ 14 ]. One report described a case of NMS with lead-pipe rigidity in the setting of recent cocaine use by a chronic cocaine user with long-term antipsychotic treatment [ 15 ]. Another case of classic NMS was due to cocaine use that occurred in the absence of antipsychotic medications [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 NMS is a clinical diagnosis manifested by a spectrum of symptoms, including the tetrad of hyperpyrexia, rigidity, autonomic instability, and altered consciousness. 1,2 The diagnosis of NMS consists of an elevated creatine kinase greater than 4 times the upper limit of normal is consistent with NMS, 1 and a creatine kinase level >10 000 U/L may be useful in the diagnosis of NMS. 3 Patients may also present with leukocytosis, hepatic failure, renal failure, and heart failure, as well as broad electrolyte disturbances, including hypocalcemia in the absence of infections or other known causes.…”
mentioning
confidence: 99%